Mompreneur: The Effect of Job Satisfaction on Psychological Well-Being of Mother Owning MSMEs - Krisnauli, Vallerie Waldine; Kadiyono, Anissa Lestari; Harding, Diana (Journal of Family Sciences, 2024)
Not a few mothers who work in a formal work environment decide to quit and start a new career and become entrepreneurs, which makes them part of the phenomenon often known as "mompreneur," which is a combination of her mother role and her chosen entrepreneurial role, which adequately illustrates the complexity of the responsibilities and roles that mothers play daily. With the enormous responsibility of being a mother and the center of the family, a mother's job satisfaction and psychological well-being as she goes about her day are very important. This study was conducted on 89 mompreneurs in Bandung City with a quantitative non-experimental approach through a written questionnaire conducted via small groups of mompreneurs. This study proved that job satisfaction significantly affects psychological well-being and found that job satisfaction is negatively related to marital status. In contrast, Psychological well-being is positively related to education. This study suggests that mompreneurs' socioeconomic situation does not significantly affect their job satisfaction and well-being. At the same time, most previous research focuses on the boarder concept of working mothers.